2018
DOI: 10.1371/journal.pone.0200803
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the roots of antagony in the safe male circumcision partnership in Botswana

Abstract: BackgroundPartnerships in global health and development governance have been firmly established as a tool to achieve effective outcomes. Botswana implements Safe Male Circumcision (SMC) for HIV prevention through a North-South partnership comprising the local Ministry of Health, US Centers for Disease Control and Prevention (funded by PEPFAR) and Africa Comprehensive HIV/AIDS Partnership (funded by the Bill and Melinda Gates Foundation). The SMC partnership experienced significant antagony and the aim of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…Previous studies show that if not carefully and intentionally designed, cross cultural learning experiences and partnerships have the potential to reinforce bias, stereotypes, paternalistic actions, and a superior-inferior dichotomy. 39 - 42 In this study as the results has demonstrated, exchange participants were largely aware of their biases both at professional and individual level and therefore were aware that such exchange collaborative programs could lead to cultural imposition and power domination. 17 , 43 For example, we have heard Marte and Hege expressing that they realized early that they needed to respect and understand the Malawian ways of doing things first in order for the Malawians to pay attention to their contributions.…”
Section: Discussionmentioning
confidence: 70%
“…Previous studies show that if not carefully and intentionally designed, cross cultural learning experiences and partnerships have the potential to reinforce bias, stereotypes, paternalistic actions, and a superior-inferior dichotomy. 39 - 42 In this study as the results has demonstrated, exchange participants were largely aware of their biases both at professional and individual level and therefore were aware that such exchange collaborative programs could lead to cultural imposition and power domination. 17 , 43 For example, we have heard Marte and Hege expressing that they realized early that they needed to respect and understand the Malawian ways of doing things first in order for the Malawians to pay attention to their contributions.…”
Section: Discussionmentioning
confidence: 70%
“…Literature that confirms how societal and cultural issues may affect compliance to standards for MMC could not be found. However, the available literature confirms the antagonism between MMC and traditional initiation (Katisi & Daniel, 2018).…”
Section: Discussionmentioning
confidence: 95%
“…However, traditional initiation is practiced as part of the rites to passage into adulthood (Bulled, 2014 ). Therefore, MMC is viewed as being in competition with the initiation schools (Katisi & Daniel, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…But the scope of global health clearly includes health inequities and disparities in North America as well. Therefore, global health has an ethical obligation to facilitate a conversation about its own inequalities and colonial tendencies (Eichbaum et al, 2019;Katisi & Daniel, 2018;Matenga et al, 2019;Pai, 2019). Challenging global health faculty and researchers to explore humanities pedagogies and content can spark this critical turn.…”
Section: Challenges For Building a Global Health Humanitiesmentioning
confidence: 99%